Relationship between dietary inflammatory index, hs-CRP level in the second trimester and neonatal birth weight: a cohort study - Yang, Yuanyuan; Kan, Hongyan; Yu, Xiaoling; Yang, Yuying; Li, Li; Zhao, Mei (Journal of Clinical Biochemistry and Nutrition, 2020)
The aim of this study was to investigate whether diet plays a role in the effect of inflammation on birth weight. The normal pre-pregnancy body mass index and healthy single pregnant women without classical inflammatory were recruited at 16–20 weeks of pregnancy and provided blood sample to measure plasma high sensitive C-reactive protein (hs-CRP) level. The Dietary Inflammatory Index (DII) score was calculated by a three-day 24 h recall method, and a cohort of 307 eligible pregnant women was established. According to birth weight, the subjects were divided into three groups: normal birth weight (NBW) group, low birth weight (LBW) group, and high birth weight (HBW) group. The hs-CRP level and DII score were significantly different between NBW and LBW groups. The risk of higher hs-CRP in the pro-inflammatory dietary group was 1.89 times than the control group (95% CI: 1.05, 3.42). The risk of LBW with higher hs-CRP was 3.81 times than normal hs-CRP (95% CI: 1.26, 11.56). The risk of LBW in the pro-inflammatory dietary group was 10.44 times than in the anti-inflammatory dietary group (95%CI: 1.29, 84.61). The pro-inflammatory dietary in the second trimester affects the hs-CRP level, showing a positive correlation. And both of two factors increase the risk of LBW.